The Flow of Refugees and International Terrorism – Primarily a European Problem, but with Historical Roots and Geopolitical Dimensions - Stoyanov, Velcho (Research Papers, 2016)
It is indisputable that the issue of refugees and terrorism is becoming more and more topical and most of all – a European problem, but with much broader dimensions that already have a geopolitical nature. However, it gains even larger topicality and significance after the two tragic terrorist attacks that were carried out in Paris and Brussels in November 2015 and March 2016 respectively. Unfortunately, however, when analyzed and commented upon, and during the attempts to counteract, solve and overcome these tragic events, some historical roots and the fundamental reasons that provoke them are underestimated and even downright ignored. This is precisely the purpose of the present study: first, to pay attention to their historical “roots”; and second, to attempt to reveal their fundamental prerequisites, motives and reasons, but in the most synthesized way possible, because the subject matter and the problems are quite extensive and complex.
Keywords: Refugees; International terrorism; Geopolitics; Islamism; Liberal economics; Social state; Secret political societies